2018
DOI: 10.1146/annurev-med-050715-105122
|View full text |Cite
|
Sign up to set email alerts
|

Zika, Chikungunya, and Other Emerging Vector-Borne Viral Diseases

Abstract: Arthropod-borne viruses (arboviruses) have a long history of emerging to infect humans, but during recent decades, they have been spreading more widely and affecting larger populations. This is due to several factors, including increased air travel and uncontrolled mosquito vector populations. Emergence can involve simple spillover from enzootic (wildlife) cycles, as in the case of West Nile virus accompanying geographic expansion into the Americas; secondary amplification in domesticated animals, as seen with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
332
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(349 citation statements)
references
References 101 publications
(120 reference statements)
2
332
0
15
Order By: Relevance
“… Arthritogenic alphaviruses comprise a group of enveloped RNA viruses that are transmitted to humans by mosquitoes and cause debilitating acute and chronic musculoskeletal disease 1 . The host factors required for alphavirus entry remain poorly characterized 2 .…”
mentioning
confidence: 99%
“… Arthritogenic alphaviruses comprise a group of enveloped RNA viruses that are transmitted to humans by mosquitoes and cause debilitating acute and chronic musculoskeletal disease 1 . The host factors required for alphavirus entry remain poorly characterized 2 .…”
mentioning
confidence: 99%
“…The increasing number of outbreaks caused by arboviruses, such as DENV, ZIKV and CHIKV, has placed tremendous pressure on scientists worldwide to generate therapeutic agents or vaccines in response to the epidemics (Weaver et al, 2018). Cryo-EM has been applied extensively to study the structures of virion-antibody complexes which have provided insights into the molecular basis of antibody-mediated neutralization mechanisms and the identification of potential therapeutic immunogens.…”
Section: Neutralizationmentioning
confidence: 99%
“…In the case of mosquito‐borne viruses, insecticide resistance, poor sanitation, unplanned urbanization, and inadequate health services have also contributed to the endemicity of arboviruses in many regions of the world. Of these, dengue virus (DENV) and Zika virus (ZIKV) (genus Flavivirus ), which are spread by mosquitos of the Aedes spp ., are endemic in Asia, Africa, and Latin America, but multiple outbreaks have also recently occurred in Europe as a result of the spreading urge of the vectors . Current estimates indicate about 300–500 million DENV infections each year.…”
Section: Figurementioning
confidence: 99%
“…Of these, dengue virus (DENV) and Zika virus (ZIKV) (genus Flavivirus), which are spread by mosquitos of the Aedes spp.,a re endemic in Asia, Africa, and Latin America,b ut multiple outbreaks have also recently occurred in Europea saresulto ft he spreading urge of the vectors. [2] Currente stimates indicate about 300-500m illion DENV infections each year.A lthough the mortality rate of many flavivirus infectionsi sr elatively low (roughly2 .5 %), these infections can cause severe disease, such as microcephalyinfetuses and Guillain-BarrØ syndrome in adults that are caused by the host's immune response to the neurotropic ZIKV, [3] or hemorrhagicf ever or shock in the case of the non-neurotropic DENV. [4] Recent studies also found high loads of flavivirus RNA (DENV,Z IKV) in breast milk and saliva, suggesting that these vertical and sexual transmissionr outes can also contribute to the increased spreading of these viruses.…”
mentioning
confidence: 99%